Functional Multipotency of Stem Cells and Recovery Neurobiology of Injured Spinal Cords. Issue 4 (April 2019) - Teng, Yang D.
This invited concise review was written for the special issue of Cell Transplantation to celebrate the 25th anniversary of the American Society for Neural Therapy and Repair (ASNTR). I aimed to present a succinct summary of two interweaved lines of research work carried out by my team members and collaborators over the past decade. Since the middle of the 20th century, biomedical research has been driven overwhelmingly by molecular technology-based focal endeavors. Our investigative undertakings, however, were orchestrated to define and propose novel theoretical frameworks to enhance the field's ability to overcome complex neurological disorders. The effort has engendered two important academic concepts: Functional Multipotency of Stem Cells, and Recovery Neurobiology of Injured Spinal Cords. Establishing these theories was facilitated by academic insight gleaned from stem cell-based multimodal cross-examination studies using tactics of material science, systems neurobiology, glial biology, and neural oncology. It should be emphasized that the collegial environment cultivated by the mission of the ASNTR greatly promoted the efficacy of inter-laboratory collaborations. Notably, our findings have shed new light on fundamentals of stem cell biology and adult mammalian spinal cord neurobiology. Moreover, the novel academic leads have enabled determination of potential therapeutic targets to restore function for spinal cord injury and neurodegenerative diseases.